Cinematic Rehearsals of Phenomenology: On the Ontic-Ontological Schema and Heideggerian Film Theory - John Rhym (Film-Philosophy, 2024)
This article argues that the strengths and problems of Shawn Loht's Phenomenology of Film: A Heideggerian Account of the Film Experience (2017) are rooted in its method, which derives from a specific interpretation of Heidegger's existential analytic and from the critical strategy implemented by Heidegger – and thus later adopted by his readers and applied to various disciplinary domains – in his polemical engagement with the history of philosophy. Central to this method is what I refer to as the ontic-ontological schema, and the article maps out the ways in which it operates in Loht's book: how it shapes his critical intervention into film studies and his claims about film ontology and spectatorship. My argument is that the ontic-ontological schema, while allowing the author to make interesting inroads into debates in film-philosophy, nonetheless undermines the coherence and efficacy of his claims about the cinematic experience as well as his attempts to mobilize these claims in the analysis of specific films. That is, Loht's disciplinary application of the ontic-ontological schema makes for a compelling discursive polemic, but it also exposes a crucial conceptual incompatibility in the work's configuration of and navigation between ontology, aesthetics, and criticism.